(3GddWGFa GdSfjI aj TQM GdebGeGJ GdMQjQjIs - (3CMeO Hf jhSa GdchGRj GdYHGSj GdHUQjs; (3GdbGSe Hf Ydj Hf eMeO Hf YKeGf, CHh eMeO GdMQjQj GdHUQj,J (B516 (3g` s
(3ChdgG (B:s
(3hHYO, aEf GdebGeGJ GdJj CfTCgG YdGeI GdCYdGe GdMQjQj s
(3BNQgG (B:s
(3MjK ef YdjfG HEceGdg, hhabfG dLeYg, fSCdg SHMGfg Cf jef YdjfG HfaYg s
(3HChdgG hBNQgG JedjcGJ eJCNQIs
(3hHChdgG agQS ddebGeGJ hHYV ehVhYGJ GdTQM hHgG fXGe GdJYbjHIs
(3cJHgG GdeDda HfaSgs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs